Rethinking language faculty. Has language evolved for other than language related reasons? - Wróbel, Szymon (Theoria et Historia Scientiarum, 2012)
Attempting to give a straightforward answer to the question, I put forward in this paper – Has language evolved for other than language related reasons?, I would emphatically say – No, it has not!, as long as language has still anything to do with symbolic expression of a person’s thoughts – that is, making them public, as well as symbolic exchange, which next to the exchange of goods, and next to the exchange of women, is, according to antropologists, the cornerstone of our culture. But if we understand language as a system of internal computations in a living organism, which are based on recursion and resemble a prototype of general intelligence, and which can be used in the domain of social exchange of goods, perception of kinship, communication, counting livestock, navigation, and setting order in a sentence, then I would have to affirmatively say – Yes, it has! Do these skills have anything to do with language seen as a means of communication or language seen as a paring of sound and meaning? Well, probably no more than the exchange of goods has to do with the exchange of symbols. I draw the general conclusion: in my initial question – Has language evolved for other than language related reasons? – the most important concept is not that of evolution or the faculty of language, but what I call “language related reasons,” as it means anything we may wish it to, depending on what is meant by “language.”